Performances comparison of enantiomeric separation materials prepared from shrimp and crab shells. (15th January 2019) - Yang, Fei; Cai, Ming-Lan; Chen, Wei; Bai, Zheng-Wu
Highlights: Chiral separation materials were prepared from chitins of shrimp and crab shells. The materials derived from shrimp and crab shells showed close solvent tolerability. The materials with the same substituent had comparable separation performances. Suprastructures of the materials should be very similar. The two chitins may be both applicable to prepare chiral separation materials. Abstract: Previously reported studies demonstrate that many chitin/chitosan derivatives are promising for enantioseparation of chiral compounds. The aim of the present study is to investigate influence of the chitin sources on performances of the chitosan type enantiomeric separation materials. Therefore, the chitosans were prepared from crab and shrimp shells, from which two sets of chiral selector, i.e. chitosan bis(3, 5-dimethylphenylcarbamate)-(octanamide)s and chitosan bis(3, 5-dichlorophenylcarbamate)-(octanamide)s were synthesized. The chitosan bis(3, 5-dimethylphenylcarbamate)-(octanamide)s, respectively, derived from crab and shrimp shells were close in swelling capacity and enantioseparation capability, and the same feature was found for the other two chiral selectors of chitosan bis(3, 5-dichlorophenylcarbamate)-(octanamide). On the other hand, although most of the chiral analytes were eluted out in the same elution order, there were two analytes were in reversed elution orders when separated by the two chiral stationary phases of chitosan bis(3, 5-dichlorophenylcarbamate)-(octanamide). Based on the observed results, we conclude that enantiomeric separation materials may be developed either with shrimp chitin or crab chitin, depending on the source accessibility.